Association of Severe Traumatic Brain Injury Patient Outcomes With Duration of Cerebrovascular Autoregulation Impairment Events. Issue 1 (July 2016) - Preiksaitis, Aidanas; Krakauskaite, Solventa; Petkus, Vytautas; Rocka, Saulius; Chomskis, Romanas; Dagi, Teodoro Forcht; Ragauskas, Arminas
Abstract : BACKGROUND: Cerebrovascular autoregulation (CA) is an important hemodynamic mechanism that protects the brain against inappropriate fluctuations in cerebral blood flow in the face of changing cerebral perfusion pressure. Temporal CA failure is associated with worse outcomes in various acute neurological diseases. An integrative approach is presently used according to the existing paradigm for the association of series of temporal CA impairments with the outcomes of patients with traumatic brain injury (TBI). OBJECTIVE: To explore the influence of the duration of CA impairment events on severe TBI patient outcomes. Patient age was also included in the analysis of the prospectively collected clinical data. METHODS: CA monitoring included 33 prospective severe TBI patients. The pressure reactivity index [PRx(t)] was continuously monitored to collect information on the dynamics of CA status and to analyze associations between the duration of the longest CA impairment event and patient outcomes. RESULTS: The Glasgow outcome scale and the duration of the longest CA impairment were negatively correlated. The duration of autoregulation impairment significantly correlated with worse outcomes. Multidimensional representation of Glasgow outcome scale plots showed that better outcomes were obtained for younger patients (age < 47 years) and those whose longest CA impairment event was shorter than 40 minutes if PRx(t) was above 0.7 in the CA impairment event. CONCLUSION: Unfavorable outcomes for TBI patients are more significantly associated with the duration of the single longest CA impairment episode at a high PRx(t) value, rather than with averaged PRx(t) values or the average time of all CA impairment episodes. ABBREVIATIONS: ABP, arterial blood pressure ABP(t), continuous reference arterial blood pressure CA, cerebrovascular autoregulation CBF, cerebral blood flow CPP, cerebral perfusion pressure GOS, Glasgow outcome scale GOS HD, Glasgow outcome scale after hospital discharge GOS 6M, Glasgow outcome scale at 6 months after discharge ICP, intracranial pressure ICP(t), continuously monitored intracranial pressure LCAI, longest CA impairment optCPP, optimal cerebral perfusion pressure PRx(t), pressure reactivity index TBI, traumatic brain injury